Health condition analysis in adults with surgically corrected congenital heart defect (on the example of atrioventricular canal defect) - Malska, Andriana (ScienceRise: Medical Science, 2017)
The estimation of the surgery was carried out, the most common forms of the disorder, which occur after surgical treatment in adult patients with atrioventricular communication, were determined. The aim of research was to investigate the main clinical and echocardiography changes occurred in adults after surgery directed to atrioventricular communication for the further dispensary system improvement. Methods. Retrospective analysis of the spread of congenital heart disease - atrioventricular communication in 12 adults aged 18-28 years treated in Municipal Institution Lviv Regional Children's Hospital during 2009-2016. Statistical methods included relative and average values calculation, their average errors, the assessment of the probability of difference between the obtained results in the comparable groups using Student's t test. Results. It was found that both men and women after atrioventricular communication surgical treatment in childhood had poor quality of life due to physical and emotional condition worsening. Significant part of the patients still suffered from mitral and tricuspid insufficiency, heart failure of 1-2 degree, pulmonary artery regurgitation of 1 degree, and chamber hypertrophy. Conclusion. The mentioned group of patients needs lifelong medical care by specialists (cardiologists, surgeons, psychologists, physitians and other) for timely qualified care, prescriptions determination, and reoperations within optimal terms